Effect of dietary administration ofmethyltestosterone on the growth and sexreversal of two ornamental fish species - James, R; Sampath, K (Indian Journal of Fisheries, 2014)
Efficacy of androgenic hormone, methyltestoterone (MT) on growth, sex reversaland reproductive performance of two ornamental fishes, red swordtailXiphophorus helleri and siamese fighting fish Betta splendens were investigated.30 day old juveniles were fed ad libitum on diets containing different levels ofMT (0,10,20,40 and 60 mg kg-1 diet) during the experimental period. The meanbody weight and length and specific growth rate of X. helleri and B. splendenswere higher in the MT 10 mg kg-1 treated groups than other levels of MT treatedgroups, and hence 10 mg kg-1 is considered as optimum dose for attaining highergrowth rate. Sex determination of the fishes based on the secondary sexualcharacteristics showed increased percentage of males with higher dose levels ofMT-treated groups. B. splendens treated with 20,40,60 mg kg-1 produced 100%male population on day 84,56 and 56, respectively, while X. helleri treated with40 and 60 mg kg-1 produced 100% male population on day 70 and 56.